(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article presents several questions concerning the use of theatrical work documents, specifically focusing on stage lighting, as a source for research in the field of performing arts, especially in the history of theater. Thus, based on a collection of documents related to the stage lighting of the production of Vestido de noiva by Nelson Rodrigues, staged by Os Comediantes (1943, 1944, and 1947), these questions are introduced and illustrated through initial analyses that highlight what these documents are and their potential. With a focus on three primary documents – a typewritten script of the play, its first edition, and the lighting operation script – it presents various perspectives on the history of this significant theatrical work.